Outcome of transsphenoidal surgery for acromegaly using strict criteria for surgical cure. - Sheaves, R; Jenkins, P; Blackburn, P; Huneidi, A; Afshar, F; Medbak, S; Grossman, A; Besser, G; Wass, J (1996)
OBJECTIVE: Previous studies of surgical treatment for acromegaly have used varied criteria for 'cure', but elevated GH levels are considered to be associated with continuing disease activity. We wished to analyse the results of transsphenoidal pituitary surgery for acromegaly and assess the longer-term outcome for patients not offered further treatment when post-operative levels of GH < 5 mU/l were achieved. DESIGN: We studied a retrospective group of patients who underwent transsphenoidal surgery for acromegaly at St Bartholomew's Hospital between 1985 and 1993. PATIENTS: One hundred consecutive patients (53 male, mean age 46 years, range 18-68 years) undergoing transsphenoidal surgery for acromegaly were assessed. The patients were followed for a mean of 3.8 years (range 0.5-8 years) after operation. MEASUREMENTS: GH levels are represented as a mean value from a four-point day curve taken at 0830, 1300, 1700 and 1900 h. ACTH reserve was assessed basally and, if this was normal, with the insulin tolerance or glucagon tests. TSH, T4, PRL, LH, FSH, testosterone or oestradiol and plasma and urine osmolality were also measured. RESULTS: Post-operatively, 42% of patients achieved a mean GH level of < 5 mU/l. The success of surgery was related to the preoperative GH level; 65% of the patients with preoperative GH levels < 20 mU/l but only 18% of the patients with GH levels > 100 mU/l achieved post-operative GH values < 5 mU/l. In addition, tumour size influenced the outcome of surgery with 61% of patients with a microadenoma but only 23% of patients with a macroadenoma achieving post-operative GH levels of < 5 mU/l. Of the 42 patients considered in remission post-operatively (mean GH < 5 mU/l), 32 were available for long-term follow-up and were not offered any further treatment: only one of these has shown evidence of mild biochemical recurrence after a mean follow-up of 3.8 years (range 0.5-8). There were no peri-operative deaths. Two patients required surgical repair for CSF leaks and there were eight documented cases of meningitis. Permanent diabetes insipidus was noted in eight patients post-operatively. New anterior pituitary deficiency occurred in 21% of patients following surgery; 73% had unaltered pituitary function and in 6% recovery of partial hypopituitarism was noted. CONCLUSIONS: The stated outcome of surgery depends on the criteria adopted. Safe GH levels (mean levels < 5 mU/l) can be achieved in 42% of an unselected series of patients with acromegaly and if the tumour is a microadenoma this figure rises to 61%. Based on the current evidence it is safe not to offer further treatment to those patients in whom post-operative GH < 5 mU/l are achieved.